“PLAN DE MARKETING DE LA FERRETERÍA MAGALY ROMÁN DE LA CIUDAD DE LOJA.” PARA LOGRAR EL POSICIONAMIENTO EN EL MERCADO. - Guaman Guaillas, Cristian Roberto (2019)
The increase in sales and sales of equipment, tools and materials for construction, demonstrate the constant development of hardware stores nationwide. In the same way, the competence of the hardware sector is another factor that is increasing, so decisions must be made regarding: implementing strategies that will counteract the competition, seeking to solve this problem, the proposal was proposed of the elaboration of a marketing plan for the hardware store Magaly Román, through which it is intended to publicize a series of commercial and advertising strategies in order to increase customer acceptance and positioning in the market. For the development and fulfillment of the present investigation, the following research methods were required: synthetic method: through the theoretical frame, the inductive method could be proposed; with which the current situation of the hardware store and the Deductive Method could be identified, which allowed the external analysis to be identified, identifying opportunities and threats to the environment in which the company operates, as well as using information gathering techniques such as: direct observation which allowed to know of the current situation of the hardware store, the survey, which was applied to the 240 external customers at random, in the same way it applied 6 surveys to its collaborators and 9 to the different hardware stores in the city of Loja. Through these techniques it was possible to compile truthful information for the development of this work. Using the information provided by the surveys applied to the different hardware stores, the Evaluation Matrix of External Factors (EFE) could be proposed, which gave a weighted total value of 2.82, demonstrating that the opportunities outweigh the threats and that the external environment is favorable to the hardware store. For the elaboration of the Competitive Profile Matrix (MPC), the analysis of the 5 Porter forces was carried out in which it was possible to identify that Mega Hierro is one of the best positioned hardware companies in the Lojano 5 market, due to the quality of service, financing, prices, guarantees, location and participation in the market giving a weighted rating within the MPC matrix of 3.45, this being the highest score. With the results obtained in the survey of internal and external clients, the matrix of Internal Factor Evaluation (EFI) could be elaborated, which gave a result of 2.59, proving that the strengths are favorable with respect to the weaknesses. With the results obtained in the EFE and EFI shade, the SWOT analysis was carried out, obtaining strengths such as: the hardware store offering quality products, its location is adequate, it has qualified personnel; The weaknesses identified were: little product information, no established promotion plan, lack of substitute products; their opportunities are: government support, investment in the construction sector, incorporation of new technologies and their threats are: excess of procedures for credits, increase of the poverty index, high costs of new technologies, from this comparison a series was obtained strategic objectives such as: develop a promotional plan, an advertising plan, establish pricing strategies, increase the product portfolio and design a training program, in order to develop the hardware will make an investment of $ 4,679.70 dollars. Which will contribute to the fulfillment of the general objective that is the positioning of the hardware store in the market.